The blending of fact and fiction in three American documentary (crime) narratives - Flis, Leonora (Acta neophilologica, 2010)
The article focuses on narratives that can best be classified as documentary novels. Such narratives can frequently depict deviant crimes. The selected texts are taken from three different decades, as the study intends to determine if/how the perception of crime and, consequently, its depiction in verbal narratives change through time, and moreover, to examine the attitudes of different writers towards facts (empirical reality) that they depict. Truman Capotećs In Cold Blood (1965), Norman Mailerćs The Executionerćs Song (1979), and John Berendtćs Midnight in the Garden of Good and Evil: A SavannahStory (1994) are all instances of crime narratives that blur and thus problematize the (often thin) line between fact and fiction, and, as a result,raise issues that concern genre theory. These texts embody characteristics of journalistic, historical, (auto)biographical, and fictionalaccounts, and continually oscillate on the scale of factuality or fictionality.
Keywords: "In cold blood"; "Midnight in the garden of good and evil"; "The executioner's song"; American literature; American novel; ameriška književnost; ameriški roman; Berendt, John, 1939-; Capote, Truman, 1924-1984; crime novel; documentary novel; dokumentarni roman; kriminalni roman; Literarne študije; Mailer, Norman, 1923-2007